2015
DOI: 10.5455/medscience.2015.04.8272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Dexamethasone to Bupivacaine on Transversus Abdominis Plane Block [Transversus Abdominis Plane Bloga Eklenen Deksametazonun Etkisi]

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
6
0
2
Order By: Relevance
“…All 9 RCTs compared the TAP block using LA with dexamethasone versus LA alone. All studies used a long-acting LA for the TAP block, including bupivacaine in 3 studies [ 26 , 28 , 29 ], ropivacaine in 5 studies [ 16 , 17 , 24 , 25 , 30 ], and levobupivacaine in 1 study [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 9 RCTs compared the TAP block using LA with dexamethasone versus LA alone. All studies used a long-acting LA for the TAP block, including bupivacaine in 3 studies [ 26 , 28 , 29 ], ropivacaine in 5 studies [ 16 , 17 , 24 , 25 , 30 ], and levobupivacaine in 1 study [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering our literature review, it can be stated that researchers generally apply unilateral TAP block for adult patients using 15-30 ml local anesthetic agents in varying concentrations [10][11][12][13]. Bupivacaine, ropivacaine, and levobupivacaine are usually preferred local anesthetic agents for TAP block [1,14].…”
Section: Discussionmentioning
confidence: 99%
“…Several adjuvant agents (including epinephrine, clonidine, buprenorphine, tramadol, dexamethasone, dexmedetomidine, neostigmine) are added to local anesthetics in regional and peripheral block applications to provide effective, long and safe analgesia at one time [9]. Only a few studies have investigated the addition of local anesthetics for TAP block such as dexamethasone [11], epinephrine [12], fentanyl [15], and dexmedetomidine [16,17]. Previous studies have reported significantly lower postoperative morphine consumption in the dexmedetomidine group [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…8 Penambahan deksametason pada anestetik lokal telah dilakukan pada beberapa penelitian yang membuktikan bahwa waktu kebutuhan analgesik pertama lebih panjang dan skor nyeri lebih rendah pada grup deksametason dibanding dengan grup kontrol. 3,9 Penelitian ini bertujuan untuk membandingkan waktu kebutuhan analgesik pertama dan skor nyeri antara blok TAP panduan ultrasonografi memakai bupivakain 0,25% dengan kombinasi bupivakain 0,25% dan deksametason 8 mg.…”
Section: Pendahuluanunclassified
“…Hal ini sejalan dengan beberapa penelitian lain yang menunjukkan waktu kebutuhan analgesik pertama lebih panjang pada blok TAP kombinasi bupivakain dan deksametason dibanding dengan bupivakain. 3,9 Vasokonstriksi dapat terjadi karena efek glukokortikoid dalam memengaruhi reaktivitas vaskular dengan cara menghambat produksi vasodilator seperti prostasiklin dan nitric oxide, potensiasi respons vasoaktif terhadap katekolamin melalui reseptor glukokortikoid, serta meningkatkan respons kortisol yang berhubungan dengan peningkatan sensitivitas kontraksi arteri. 15 Efek vasokonstriksi tersebut menyebabkan penurunan absorpsi sistemik sehingga terjadi pemanjangan waktu blok saraf oleh anestetik lokal.…”
Section: Pembahasanunclassified